Family-School Relationship: Conceptual Contributions Drawn From Evidence in Argentina - Vicente, María Eugenia (2017)
The aim of this study is to contribute to the development of education policies, curricular designs and pedagogical proposals putting forward the complex and diverse relationship between families and schools. In this sense, a qualitative analysis was carried out collecting data from 28 in-depth semi-structured interviews with state and private secondary schools headmasters between 2011 and 2015; and supplemented by the analysis of 32 scientific articles from different countries published between 2013 and 2016. The conclusions reveal that thinking of the strengthening of the family-school relationship is not only a matter of distance between parents and schools but a political issue that involves the questioning of what place the student, who is defining and carrying out their own training as a citizen, occupies in school life.